Ruptures of Dress: an analysis of Vestido Nuevo and the formation of gender identity in childhood (ModaPalavra e-periódico, 2019)
In this article we will analyze the Spanish short film Vestido Nuevo (2007), which deals with gender issues in the school context. From the perspective of fashion and cinema as cultural manifestations and their possible relations with gender studies, it is sought to problematize the issues that surround the ruptures of the modes of dress in relation to the culturally established genres in contemporary Western society. Our gaze turns to childhood, a period in which the subject's gender identity, his apprehension of the world and his place in this space of socialization is constituted. With such a focus, clothing is analyzed as language and how its use can be tied in the search for affirmation and recognition of gender identity.Similarly, cinema represents social practices that express, dialogue or challenge discourses through the screens. We conclude that the dressing choices of the protagonist of the film break with the dress code established culturally throughout the history of the clothing in relation to masculine and feminine, generating social conflicts for him, for the family and for the school.
Keywords: gender; fashion; vestido nuevo